2016
DOI: 10.1515/jaes-2016-0004
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Beam-to-Column Connections with Angles. Part 2-Numerical Analysis

Abstract: Based on the results of experimental tests, presented in the first part of this paper, Part 1-Experimental Investigations (Ghindea M., Catarig A., Ballok R.) advanced numerical simulations were performed using FEM based software Abaqus. The recently arise of high speed computers and advanced FEM software packages allow to create and solve extensively detailed 3D models. The aim of this second part of the paper is to develop accurate FEM models for better approach of the studied beam-to-column connections. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 6 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…Considering the stiffness increase, the difference between tests ST5 and ST6 is 18%. In the experimental study of Ghindea et al [15], the difference in stiffness between tests TSDW10 and TSS10, with a 10 mm top and seat angle thickness, is only ~3%. This significant stiffness increase between tests ST5 and ST6 is probably due to the small thickness of the top and seat angles in these tests.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Considering the stiffness increase, the difference between tests ST5 and ST6 is 18%. In the experimental study of Ghindea et al [15], the difference in stiffness between tests TSDW10 and TSS10, with a 10 mm top and seat angle thickness, is only ~3%. This significant stiffness increase between tests ST5 and ST6 is probably due to the small thickness of the top and seat angles in these tests.…”
Section: Discussionmentioning
confidence: 94%
“…Figure 2 shows these joints, which will be also used to validate the proposed methodology. More information regarding the experimental work from Ghindea et al can be found in [15].…”
Section: Experimental Study Of Ghindea Et Almentioning
confidence: 99%
See 3 more Smart Citations